Freshwater algae : identification, enumeration and use as bioindicators - Bellinger, Edward G.; Sigee, David C. (John Wiley & Sons Inc., 2015)
"A fully revised edition of this popular guide combining practical material on techniques and water quality management with basic algal taxonomy and the role of algae as bioindicators"